Association between intimate partner violence and mentally unhealthy days in women in the U.S. - Danielle Broadnax; Reinetta Waldrop; Mechelle Claridy; Elaine Booker; Ernest Alema-Mensah (Georgia Southern University, 2016)
Background: In the United States (U.S.), intimate partner violence (IPV) is a serious public health concern, mainly affecting the health and well-being of women. The objective of this study was to identify the IPV and socio-demographic factors associated with mentally unhealthy days among women in the U.S. of ages ≥18 years. Methods: Data for this study were obtained from the 2007 Behavioral Risk Factor Surveillance System. Multivariable analyses were used to estimate adjusted odds ratios (AORs) and 95% confidence intervals (95% CIs) for factors associated with IPV and 14 or more mentally unhealthy days per month. Analyses were conducted using SAS 9.3. Results: The analyses show that the following factors increase the likelihood of self-reported 14 or more mentally unhealthy days: having a high school level of education or less (AOR: 1.732; 95% CI: 1.415-2.119) and having an income < $50,000. In addition, experiencing IPV such as: ever being threatened by a sex partner (AOR: 1.499; 95% CI: 1.264-1.779); having a sex partner ever attempt violence (AOR: 1.461; 95% CI: 1.224-1.743); having a sex partner ever become violent (AOR: 1.541; 95% CI: 1.303-1.823); and ever having unwanted sex with a partner (AOR: 1.929; 95% CI: 1.584-2.350) also increased the likelihood of self-reported 14 or more mentally unhealthy days per month. Conclusions: The results indicate that, for women in the U.S., IPV and socio-demographic factors have an effect on self-reported 14 or more mentally unhealthy days. Improving access to services that offer protection and guidance for women abused by their intimate partner could decrease the likelihood of selfreported 14 or more mentally unhealthy days and long-term negative mental health outcomes among women.